Preparation method and application of barium titanate powder for preparing multilayer ceramic capacitor

By selecting different barium sources and using solid phase reaction method and modification steps, nano-scale barium titanate powder was prepared, which solved the problems of uneven grain size and low specific surface area of ​​barium titanate powder in the traditional method, and significantly improved the breakdown voltage and durability of multi-layer ceramic capacitors.

CN119898807APending Publication Date: 2025-04-29SOUTHWEAT UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510101307.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The preparation of barium titanate powder by traditional solid phase method can easily lead to uneven grain size and low specific surface area, which will affect the breakdown voltage and durability of multi-layer ceramic capacitors.

Method used

Nano-scale barium titanate powder was prepared by selecting different barium sources and using solid phase reaction method, combining magnetic stirring, ball milling, ultrasonic dispersion and electric spark ignition, and the barium titanate grains were coated with modified additives to improve voltage tolerance.

Benefits of technology

The prepared barium titanate powder has a smaller particle size, a more uniform particle size distribution and a larger specific surface area, which significantly improves the breakdown voltage and durability of the multi-layer ceramic capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898807A_ABST
    Figure CN119898807A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of barium titanate powder for preparing a multilayer ceramic capacitor, which comprises the following steps: respectively preparing a barium source and ammonium bicarbonate into solutions, mixing, stirring at room temperature, standing, precipitating and filtering to obtain high-purity barium carbonate; the preparation method comprises the following steps: uniformly mixing high-purity barium carbonate and titanium dioxide, carrying out ball milling to obtain slurry, drying the slurry, grinding, sieving, calcining, and cooling to obtain barium titanate powder; the preparation method comprises the following steps: adding barium titanate powder and a modified additive into water, carrying out ultrasonic dispersion, drying to obtain mixed powder, carrying out secondary sintering on the mixed powder, and carrying out mixing and ball milling on a product obtained by sintering and bismuth stearate to obtain the modified barium titanate powder. The BaTiO3 powder is successfully and efficiently prepared from different barium sources through a solid-phase reaction method, and the BaTiO3 powder has a larger specific surface area; the metal elements added through modification can enable barium titanate crystal grains to bear higher voltage, so that the breakdown voltage of the MLCC prepared from the barium titanate powder is improved, and the durability of the MLCC is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic ceramic materials, and in particular relates to a preparation method and application of barium titanate powder for preparing multilayer ceramic capacitors. Background Art

[0002] Barium titanate is an electronic ceramic material with high dielectric constant, good ferroelectric, withstand voltage, piezoelectric and insulation properties. With its excellent electrical properties, it is widely used in the manufacture of electronic components such as multilayer ceramic capacitors (MLCC) and positive temperature coefficient thermistors (PTCR). Taking the common MLCC as an example, the size gradually decreases, and the actual size of the component is about 1 / 100 of the fingernail. Therefore, the corresponding dielectric layer thickness is also reduced to 1μm or less. The requirements for small-sized, high-capacity MLCCs are getting higher and higher, which requires barium titanate to have good dispersibility, uniformity, high dielectric constant and small grain size. Therefore, the synthesis of small-particle, tetragonal, single and uniformly dispersed barium titanate powder is of great research significance.

[0003] At present, most of the relevant research on the preparation of barium titanate powder by solid phase method is focused on optimizing the grinding method and calcination method, and there are few systematic studies on the effect of barium source type on barium titanate powder. The type of barium source used in the process of preparing barium titanate by solid phase method directly affects the crystal structure, particle size distribution, specific surface area, surface morphology and electrical properties of barium titanate. Therefore, selecting a suitable barium source is one of the keys to optimizing the performance of barium titanate. In addition, the traditional solid phase method uses a traditional one-step sintering process to mix the raw materials and sinter them at high temperature to synthesize barium titanate. The obtained barium titanate powder is easy to agglomerate, and it is difficult to control the uniformity of grain size. The specific surface area is low, resulting in a low breakdown voltage of the MLCC prepared from the barium titanate powder, which in turn leads to a decrease in the durability of the MLCC. Therefore, it is necessary to improve the preparation method of barium titanate powder to obtain barium titanate powder that can withstand high voltage to meet the needs of practical applications. Summary of the invention

[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0005] In order to achieve these purposes and other advantages of the present invention, a method for preparing nano-barium titanate powder is provided, comprising the following steps:

[0006] Step 1: prepare a barium source and ammonium bicarbonate into solutions respectively, then mix the two, stir them magnetically at room temperature, let them stand and settle, and then filter and collect a solid sample to obtain high-purity barium carbonate;

[0007] Step 2: After mixing high-purity barium carbonate and titanium dioxide evenly, add dispersant, ball milling medium and deionized water thereto, and then perform ball milling to obtain slurry. After drying the slurry, grind and sieve it, and then calcine the obtained material, and after cooling, barium titanate powder can be obtained.

[0008] Preferably, in step 1, the barium source is one of barium nitrate, barium chloride and barium hydroxide, and the molar ratio of the barium source to ammonium bicarbonate is 1-1.2:1-1.2.

[0009] Preferably, in step 2, the molar ratio of high-purity barium carbonate and titanium dioxide is 0.995-1.008:1, the dispersant is 0.1-5wt% of the total amount of high-purity barium carbonate and titanium dioxide, and the mass ratio of deionized water, the total amount of high-purity barium carbonate and titanium dioxide, and the ball milling medium is 1.5-2:1:5.

[0010] Preferably, in step 2, the ball milling medium is zirconia balls, and the composition of the zirconia balls is During ball milling, the mixed material is placed in a polytetrafluoroethylene ball mill and stirred and mixed by a planetary ball mill at 400 to 800 rpm for 2 to 4 hours.

[0011] Preferably, in step 2, the drying temperature is 80-120°C, the drying time is 1-2 hours, the temperature is increased to 900-1100°C at a heating rate of 5°C / min during calcination, the temperature is increased by 50°C each time, and the temperature is kept at the target temperature for 2-4 hours.

[0012] Preferably, the barium titanate powder obtained in step 2 is modified by adding the barium titanate powder and the modified additive into water for ultrasonic dispersion, drying to obtain a mixed powder, sintering the mixed powder for a second time, mixing the sintered product with bismuth stearate and ball milling to obtain a modified barium titanate powder.

[0013] Preferably, the specific method of secondary sintering is: using electric spark discharge to ignite the mixed powder. During the secondary sintering ignition, one pole of the pulse power supply is connected to the electrode rod, and the other pole is connected to the mixed powder. The automatic feeding device controls the electrode rod and the mixed powder to maintain a gap of 0.01 to 0.07 mm. The ignition time is 0.1 to 5 seconds, and the pulse power supply discharge voltage is 120 to 190V.

[0014] Preferably, the ultrasonic dispersion frequency is 30 to 60 kHz, and the dispersion time is 2 to 6 hours.

[0015] Preferably, the modifying additive is one or more of Y(Ac)3, Ho(Ac)3, Mg(Ac)2, and Dy(Ac), the amount of the modifying additive added is 1 to 5 wt% of the barium titanate powder, the amount of bismuth stearate added is 0.5 to 4 wt% of the barium titanate powder, the ball milling still uses zirconia balls as the ball milling medium, the mass ratio of the ball milling medium to the barium titanate powder is 5:1 to 1.5, and the composition of the zirconia balls is During ball milling, the mixed material is placed in a polytetrafluoroethylene ball mill and stirred and mixed by a planetary ball mill at 400 to 800 rpm for 2 to 4 hours.

[0016] The present invention also provides an application of barium titanate powder for preparing multilayer ceramic capacitors. The barium titanate powder is used for preparing multilayer ceramic chip capacitors.

[0017] The present invention has at least the following beneficial effects:

[0018] (1) The present invention successfully prepared BaTiO3 powder for preparing multilayer ceramic capacitors by solid phase reaction method using different barium sources. The powder not only has a smaller particle size and a uniform particle size distribution, but also has a larger specific surface area.

[0019] (2) The present invention also mixes the modified additives through ultrasonic dispersion, and then uses electric sparks to ignite the reactants, so that the reactants themselves burn and release heat for secondary sintering, which can effectively shorten the process route and reduce production costs. At the same time, the organic matter in the modified additives is decomposed, leaving only the added metal elements (yttrium, holmium, magnesium, dysprosium) coated on the barium titanate powder. The single barium titanate grains coated with the metal elements can withstand higher voltages, thereby increasing the breakdown voltage of the multilayer ceramic capacitor (MLCC) made from the barium titanate powder and improving the durability of the MLCC. At the same time, the introduction of bismuth stearate can reduce the viscosity of the material and prevent powder agglomeration.

[0020] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 XRD patterns of BaTiO3 powders prepared in Examples 1 to 3;

[0022] Figure 2 FTIR analysis chart of BaTiO3 powder prepared in Examples 1 to 3;

[0023] Figure 3 The SEM images and mapping images of the BaTiO3 powder prepared in Examples 1 to 3;

[0024] Figure 4The XPS total spectrum and high-resolution XPS spectrum of the BaTiO3 powder prepared in Examples 1 to 3. DETAILED DESCRIPTION

[0025] The present invention will be further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0026] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0027] Example 1

[0028] A method for preparing barium titanate powder for preparing a multilayer ceramic capacitor comprises the following steps:

[0029] Step 1: prepare barium hydroxide (Ba(OH)2) and ammonium bicarbonate (NH4HCO3) into solutions with a concentration of 0.01 mol / L, then mix 10 L of each, stir magnetically at room temperature for 30 min, let stand and precipitate, and filter to collect a solid sample to obtain high-purity barium carbonate;

[0030] Step 2: 196.34 g (1 mol) of high-purity barium carbonate and 79.87 g (1 mol) of titanium dioxide were mixed evenly, and then 2.76 g of sodium polycarboxylate, 1381.05 g of zirconium oxide balls and 414.32 g of deionized water were added thereto, wherein the zirconium oxide balls were composed of The mixed material is then placed in a polytetrafluoroethylene ball mill, stirred and mixed for 4 hours at 400 rpm by a planetary ball mill to obtain a slurry, and the slurry is dried in an oven at 80°C for 2 hours, ground and sieved, and then the obtained material is placed in a muffle furnace and heated to 1000°C at a heating rate of 5°C / min, with an interval of 50°C each time, and kept at 1000°C for 2 hours. Finally, the barium titanate powder (BaTiO3-OH) for preparing multilayer ceramic capacitors can be obtained by cooling with the furnace.

[0031] Example 2

[0032] A method for preparing barium titanate powder for preparing a multilayer ceramic capacitor comprises the following steps:

[0033] Step 1: prepare barium nitrate (Ba(NO3)2) and ammonium bicarbonate (NH4HCO3) into solutions with a concentration of 0.01 mol / L, then mix 100 L of each, stir magnetically at room temperature for 30 min, let stand and precipitate, and filter to collect the solid sample to obtain high-purity barium carbonate;

[0034] Step 2: 196.34 g (1 mol) of high-purity barium carbonate and 79.87 g (1 mol) of titanium dioxide were mixed evenly, and then 5.52 g of sucrose fatty acid ester, 1381.05 g of zirconium oxide balls and 414.32 g of deionized water were added thereto, wherein the zirconium oxide balls were composed of The mixed material is then placed in a polytetrafluoroethylene ball mill, stirred and mixed for 4 hours at 400 rpm by a planetary ball mill to obtain a slurry, and the slurry is dried in an oven at 80°C for 2 hours, ground and sieved, and then the obtained material is placed in a muffle furnace and heated to 1000°C at a heating rate of 5°C / min, with each heating interval of 50°C, and kept at 1000°C for 2 hours. Finally, the barium titanate powder (BaTiO3-N) for preparing multilayer ceramic capacitors can be obtained by cooling with the furnace.

[0035] Example 3

[0036] A method for preparing barium titanate powder for preparing a multilayer ceramic capacitor comprises the following steps:

[0037] Step 1: prepare barium chloride (BaCl2) and ammonium bicarbonate (NH4HCO3) into solutions with a concentration of 0.01 mol / L, then mix 100 L of each, stir magnetically at room temperature for 30 min, let stand and precipitate, and filter to collect a solid sample to obtain high-purity barium carbonate;

[0038] Step 2: 196.34 g (1 mol) of high-purity barium carbonate and 79.87 g (1 mol) of titanium dioxide were uniformly mixed, and then 2.76 g of sodium stearoyl lactylate, 1381.05 g of zirconium oxide balls and 414.32 g of deionized water were added thereto, wherein the zirconium oxide balls were composed of The mixed material is then placed in a polytetrafluoroethylene ball mill, stirred and mixed for 4 hours at 400 rpm by a planetary ball mill to obtain a slurry, and the slurry is dried in an oven at 80°C for 2 hours, ground and sieved, and then the obtained material is placed in a muffle furnace and heated to 1000°C at a heating rate of 5°C / min, with each heating interval of 50°C, and kept at 1000°C for 2 hours. Finally, the barium titanate powder (BaCO3-Cl) for preparing multilayer ceramic capacitors can be obtained by cooling with the furnace.

[0039] Figure 1The XRD diagrams of the BaTiO3 powders prepared in Examples 1 to 3 show that the main diffraction peaks of the samples are relatively consistent in position and intensity, indicating that the main crystal phases of the powders prepared using three different barium sources are all barium titanate (BaTiO3). Combined with the PDF standard card (NO: 79-2263), it can be determined that the samples prepared by the solid phase method this time are pure BaTiO3 powders, and the crystal structure is a tetragonal phase without other impurities. In addition, the diffraction peaks in the XRD of the three samples all show high intensity and sharp peaks, reflecting that the prepared BaTiO3 has good crystallinity. Among them, the BaTiO3 powder prepared in Example 1 using Ba(OH)2 as the barium source has the strongest and sharpest diffraction peak, indicating that the sample has the highest crystallinity.

[0040] Figure 2 FTIR analysis of BaTiO3 powder prepared in Examples 1 to 3, 3456 cm -1 The characteristic absorption peak can be attributed to the stretching vibration of OH in the water molecules adsorbed on the surface of the material. Compared with BaTiO3-Cl and BaTiO3-N, the OH stretching vibration on the surface of BaTiO3-OH is relatively strong, which means that more water molecules may be adsorbed on its surface or it may be caused by the coordination of hydroxyl and barium atoms. This also indirectly proves the feasibility of preparing BaTiO3 powder using different barium sources. At 598cm -1 The relatively strong characteristic peaks correspond to the vibration peaks of Ti-O, confirming the existence of BaTiO3 structure.

[0041] Figure 3 The SEM images of the BaTiO3 powders prepared in Examples 1 to 3 (in the figure, a is BaTiO3-OH, b is BaTiO3-N, and c is BaTiO3-Cl) clearly show that the grain sizes are all in the micrometer range. Compared with the other two samples, the BaTiO3 powder prepared with Ba(OH)2 as the barium source has smaller particle size and more uniform distribution due to its higher reaction activity. When BaCl2 is used as the barium source, the particles may be irregular in shape and accompanied by a wider particle size distribution due to the influence of by-products (such as chlorides) on the reaction process. In addition, it can be seen from the Mapping diagram that the Ba and Ti elements are evenly distributed in the three samples, further proving the successful preparation of BaTiO3-Cl, BaTiO3-N and BaTiO3-OH powders.

[0042] Example 4

[0043] In this embodiment, the prepared barium titanate powder (BaTiO3-OH) is modified on the basis of embodiment 1. The method is as follows: 200g of barium titanate powder and 5g of Y(Ac)3 are added to water and ultrasonically dispersed at 40KHz for 4h, and a mixed powder is obtained after drying. The mixed powder is sintered for a second time, and the mixed powder is ignited by electric spark discharge after drying. The discharge voltage of the pulse power supply is 180V, the gap between the electrode rod and the mixed powder is 0.05mm, the ignition time is 0.34s, and the mixed powder releases heat by itself to maintain combustion until the reaction is completed. The sintered product is mixed with 4g of bismuth stearate and 1000g of zirconium oxide balls (wherein the zirconium oxide balls are composed of The mixture was placed in a polytetrafluoroethylene ball mill, and stirred and mixed for 4 hours at 400 rpm using a planetary ball mill to obtain modified barium titanate powder.

[0044] Example 5

[0045] In this embodiment, the prepared barium titanate powder (BaTiO3-OH) is modified on the basis of embodiment 1. The method is as follows: 200g of barium titanate powder and 6g of Ho(Ac)3 are added to water and ultrasonically dispersed at 40KHz for 4h, and a mixed powder is obtained after drying. The mixed powder is sintered for a second time, and the mixed powder is ignited by electric spark discharge after drying. The discharge voltage of the pulse power supply is 180V, the gap between the electrode rod and the mixed powder is 0.05mm, the ignition time is 0.34s, and the mixed powder releases heat by itself to maintain combustion until the reaction is completed. The sintered product is mixed with 4g of bismuth stearate and 1000g of zirconium oxide balls (wherein the zirconium oxide balls are composed of ), placed in a polytetrafluoroethylene ball mill, and stirred and mixed for 4 h by a planetary ball mill at 400 rpm to obtain modified barium titanate powder.

[0046] Example 6

[0047] In this embodiment, the prepared barium titanate powder (BaTiO3-OH) is modified on the basis of embodiment 1. The method is as follows: 200g of barium titanate powder and 4g of Mg(Ac)2 are added to water and ultrasonically dispersed at 40KHz for 4h, and a mixed powder is obtained after drying. The mixed powder is sintered for a second time, and the mixed powder is ignited by electric spark discharge after drying. The discharge voltage of the pulse power supply is 180V, the gap between the electrode rod and the mixed powder is 0.05mm, the ignition time is 0.34s, and the mixed powder releases heat by itself to maintain combustion until the reaction is completed. The sintered product is mixed with 4g of bismuth stearate and 1000g of zirconium oxide balls (wherein the zirconium oxide balls are composed of ), placed in a polytetrafluoroethylene ball mill, and stirred and mixed for 4 h by a planetary ball mill at 400 rpm to obtain modified barium titanate powder.

[0048] Table 1 shows the specific surface area and pore volume of BaTiO3 powder prepared in Examples 1 to 6. The results show that BaTiO3-OH has a larger specific surface area (47.3087 m2) than BaTiO3-N and BaTiO3-Cl. 2 / g), the specific surface area and pore volume results once again proved that the BaTiO3-OH powder prepared by the solid phase reaction method is a more advantageous barium source material. Compared with the original BaTiO3 powder, the specific surface area and pore volume of the modified BaTiO3 powder are further improved.

[0049] Table 1

[0050] <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Example 1 (BaTiO3-OH)]]> 47.3087 <![CDATA[Example 2 (BaTiO3-N)]]> 2.4148 <![CDATA[Example 3 (BaTiO3-Cl)]]> 3.9201 <![CDATA[Example 4 (Modified BaTiO3-OH)]]> 49.3087 <![CDATA[Example 5 (Modified BaTiO3-OH)]]> 48.8148 <![CDATA[Example 6 (Modified BaTiO3-OH)]]> 48.9201

[0051] Comparative Example 1

[0052] The difference between this comparative example and Example 4 is that no Y(Ac)3 is added, and the rest is consistent with Example 4.

[0053] Comparative Example 2

[0054] The difference between this comparative example and Example 4 is that 200 g of barium titanate powder and 5 g of Y(Ac)3 are added to water and ultrasonically dispersed at 40 KHz for 4 h, and a mixed powder is obtained after drying. The mixed powder is sintered in a calcining furnace at a sintering temperature of 900° C. for 4 h, and the sintered product is mixed with 4 g of bismuth stearate and 1000 g of zirconium oxide balls (wherein the zirconium oxide balls are composed of ), placed in a polytetrafluoroethylene ball mill, and stirred and mixed for 4 hours by a planetary ball mill at 400 rpm to obtain nano barium titanate powder. The rest is consistent with Example 4.

[0055] Comparative Example 3

[0056] The difference between this comparative example and Example 4 is that 200 g of barium titanate powder and 5 g of Y(Ac)3 are added to water and ultrasonically dispersed at 40 KHz for 4 h, and a mixed powder is obtained after drying. The mixed powder is mixed with 4 g of bismuth stearate and 1000 g of zirconium oxide balls (wherein the zirconium oxide balls are composed of ), placed in a polytetrafluoroethylene ball mill, and stirred and mixed for 4 hours by a planetary ball mill at 400 rpm to obtain nano barium titanate powder. The rest is consistent with Example 4.

[0057] Comparative Example 4

[0058] The difference between this comparative example and Example 4 is that bismuth stearate is not added, and the rest is consistent with Example 4.

[0059] The nano-barium titanate powders obtained in Examples 1 to 6 and Comparative Examples 1 to 4 were sampled and tested, and MLCCs were made and the breakdown voltage was tested according to the following method:

[0060] Add nano-barium titanate powder, acrylate, ethanol, and zirconium oxide balls in a mass ratio of 55:5:45:20 to a ball mill and mill them together at 1200rpm for 2.5h to obtain a ceramic slurry. Use a scraper method to make ceramic green sheets. Use Ni as the main component of electrode conductive paste to screen print on the ceramic green sheets to form a conductive film. Then, stack and press the ceramic green sheets with the conductive film. Then, heat treat and sinter the ceramic stack. Apply conductive paste on the outside of the sintered body and bake it to finally obtain a multilayer ceramic capacitor (MLCC). The breakdown voltage of the MLCC product was tested at a boost rate of 200V / s. The test results are shown in Table 2:

[0061] Table 2

[0062]

[0063] As can be seen from Table 2, compared with Examples 1 to 3, the breakdown voltage of the prepared MLCCs in Examples 4 to 6 is significantly improved compared with Examples 1 to 3 due to the modification of the barium titanate powder. The breakdown voltage is high and the durability is very good. Compared with Example 4, in Comparative Example 1, the voltage that a single barium titanate grain of the nano-barium titanate powder can withstand is greatly reduced due to the lack of the modified additive. Compared with Example 4, in Comparative Example 2, the conventional sintering is used during the secondary sintering, so the modified additive in the MLCC cannot be completely removed. The organic matter decomposes, resulting in a decrease in the adhesion of the added Y element on the barium titanate, which in turn leads to a decrease in the voltage that a single barium titanate grain can withstand. Compared with Example 4, Comparative Example 3 does not perform secondary sintering, resulting in the added Y(Ac)3 not being able to effectively adhere to the barium titanate, which in turn leads to a decrease in the voltage that a single barium titanate grain can withstand. Compared with Example 4, Comparative Example 4 does not add bismuth stearate, resulting in agglomeration of the nano barium titanate powder finally obtained, which has a slight effect on the voltage that a single barium titanate grain can withstand.

[0064] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for preparing barium titanate powder for preparing multilayer ceramic capacitors, characterized in that: The following steps are involved: Step 1: prepare a barium source and ammonium bicarbonate into solutions respectively, then mix the two, stir them magnetically at room temperature, let them stand and settle, and then filter and collect a solid sample to obtain high-purity barium carbonate; Step 2: After mixing high-purity barium carbonate and titanium dioxide evenly, add dispersant, ball milling medium and deionized water thereto, and then perform ball milling to obtain slurry. After drying the slurry, grind and sieve it, and then calcine the obtained material, and after cooling, barium titanate powder can be obtained.

2. The method for preparing barium titanate powder for preparing multilayer ceramic capacitors according to claim 1, characterized in that: In the step 1, the barium source is one of barium nitrate, barium chloride and barium hydroxide, and the molar ratio of the barium source to ammonium bicarbonate is 1-1.2:1-1.

2.

3. The method for preparing barium titanate powder for preparing multilayer ceramic capacitors according to claim 1, characterized in that: In the step 2, the molar ratio of high-purity barium carbonate and titanium dioxide is 0.995-1.008:1, the dispersant is 0.1-5wt% of the total amount of high-purity barium carbonate and titanium dioxide, and the mass ratio of deionized water, the total amount of high-purity barium carbonate and titanium dioxide, and the ball milling medium is 1.5-2:1:

5.

4. The method for preparing barium titanate powder for preparing multilayer ceramic capacitors according to claim 3, characterized in that: In the step 2, the ball milling medium is zirconia balls, and the composition of the zirconia balls is φ3mm:φ5mm=2:

3. During ball milling, the mixed material is placed in a polytetrafluoroethylene ball mill jar and stirred and mixed for 2 to 4 hours at 400 to 800 rpm using a planetary ball mill.

5. The method for preparing barium titanate powder for preparing multilayer ceramic capacitors according to claim 1, characterized in that: In the step 2, the drying temperature is 80-120° C., and the drying time is 1-2 hours. During calcination, the temperature is increased to 900-1100° C. at a heating rate of 5° C. / min, with each heating interval of 50° C., and the temperature is kept at the target temperature for 2-4 hours.

6. The method for preparing barium titanate powder for preparing multilayer ceramic capacitors according to claim 1, characterized in that: The barium titanate powder obtained in step 2 is modified by adding the barium titanate powder and the modified additive into water for ultrasonic dispersion, drying to obtain a mixed powder, sintering the mixed powder for a second time, mixing the sintered product with bismuth stearate and ball milling to obtain a modified barium titanate powder.

7. The method for preparing barium titanate powder for preparing multilayer ceramic capacitors according to claim 6, characterized in that: The specific method of secondary sintering is: use electric spark discharge to ignite the mixed powder. During the secondary sintering ignition, one pole of the pulse power supply is connected to the electrode rod, and the other pole is connected to the mixed powder. The automatic feeding device controls the electrode rod and the mixed powder to maintain a gap of 0.01 to 0.07 mm. The ignition time is 0.1 to 5s, and the pulse power supply discharge voltage is 120 to 190V.

8. The method for preparing barium titanate powder for preparing multilayer ceramic capacitors according to claim 6, characterized in that: The ultrasonic dispersion frequency is 30 to 60 kHz, and the dispersion time is 2 to 6 hours.

9. The method for preparing barium titanate powder for preparing multilayer ceramic capacitors according to claim 6, characterized in that: The modified additive is one or more of Y(Ac)3, Ho(Ac)3, Mg(Ac)2, and Dy(Ac), the added amount of the modified additive is 1-5wt% of the barium titanate powder, the added amount of bismuth stearate is 0.5-4wt% of the barium titanate powder, the ball milling still uses zirconium oxide balls as ball milling media, the mass ratio of the ball milling media to the barium titanate powder is 5:1-1.5, the composition of the zirconium oxide balls is φ3mm:φ5mm=2:3, and the mixed materials are placed in a polytetrafluoroethylene ball mill during ball milling, and stirred and mixed for 2-4 hours at 400-800rpm by a planetary ball mill.

10. An application of barium titanate powder prepared by the preparation method according to any one of claims 1 to 9 for preparing multilayer ceramic capacitors, characterized in that: The barium titanate powder is used to prepare a multilayer ceramic chip capacitor.